For him who has eyes to see : beauty in the history of theology - Rybarczyk, Edmund J. (Eugene, Oregon : Cascade Books, 2016)
Too many Christians are afraid of beauty. This fear disconnects these Christians from their larger culture, a culture that is increasingly visual, increasingly aware of the presence and power of images, and more commonly fascinated by the power of beauty and form. This historical-theological overview presents the thought of ten theologians and one philosopher in an attempt to give Christians helpful vocabulary concerning beauty and aesthetics. It is time to use beauty and aesthetics for the mission of Christ! And yet rather than simply parrot the larger post-Christian culture, Christians and churches need to employ beauty and aesthetics in a manner that echoes God's own revelation: creation and redemption through Jesus Christ. We need to develop a sensitivity that can perceive beauties ignored. We need theological framing that both respects the glory of God's handiwork and keeps it from becoming idolatrous. We need to live with wonder for the bounty that routinely surrounds us. In short, we need eyes to see. -- back cover.
Includes bibliographical references (pages 237-245).
Keywords: Aesthetics -- Religious aspects -- Christianity; Aesthetics -- History